(untitled) (Research, Society and Development, 2025)
The present article aims to plan the design of a proposal for curricular correlation in single-teacher and multigrade schools in Costa Rica, in order to present an example of didactic planning that aligns with the current demands of the educational system. It is based on the premise that effective correlation can reduce teachers’ workload, integrate knowledge, address student diversity, and facilitate the teaching–learning assessment processes in these rural schools, which represent 66% of the country’s multigrade environments. A qualitative research methodology is proposed, based on bibliographic analysis and derived from the author’s empirical reflection over thirteen years of experience as a teacher and administrator in multigrade educational settings, as well as from the systematic inquiry into the needs of single-teacher and multigrade teaching teams working in rural areas. The main outcome is the detailed design of a proposal for curricular correlation between the subjects of Science and Mathematics for the first educational cycle. This proposal offers a practical solution to the issue of curricular planning in single-teacher and multigrade environments. Finally, the article highlights some of the characteristics of single-teacher schools, their potentialities, and some of their limitations. The proposal emphasizes that curricular correlation should be flexible, creative, and take into account the particularities of the local context and the group of students, as well as the principles of Universal Design for Learning (UDL) to ensure inclusion.